Internet addiction, resilience and school performance in adolescents of Pucallpa - Sánchez-Yarmas, Elsa M. (2021)
This research had as purpose to analyze the relationship between internet adicction, resilience and school performance in adolescents from the districts of Yarinacohca and Calleria, Pucallpa city, in the región of Ucayali (Peru). This region has as characteristics to concentrate the population of adolescents with one of the lowest school performance in the country and who do neither study nor work. This study was controlled correlational and comparative. The sample was composed by 519 high school students (third, fourth and fifth grade), from 14 to 18 years old. The instruments were the Wagnild and Young´s Resilience Scale (adapted by Novella, 2002) and the Young´s Internet Addiction Test (adapted by Matalinares et al., 2012). Schools provided califications of students. Low positive correlations between internet addiction and resilience and low negative correlations between addiction and performance were found, with small or insignificant effect sizes. It is concluded that resilience does not seem  an important factor in the school performance in this group and it is necessary to carry out further research in adolescents who are out from school to contrast with these findings.